Assessment of feeding damage symptoms by black cockchafers beetle (Apogonia sp.) in RISDA nursery at Kesang Tua, Jasin, Melaka / Muhamad Haziq Dahlan - Dahlan, Muhamad Haziq (Faculty of Plantation and Agrotechnology, 2019)
Oil palm has been introduced to Malaysia in year 1911. Started of the year, oil palm plants have highly developed to become the number of important crop of the country. However there are many obstacles like beetles Apogonia sp. as the pest in oil palm nursery that affected leaves will appear to dry out and generally plant growth is thinner and irritated. This study is to assess the rate of feeding damage of this pest and to determine the damage categories in different sampling layer at RISDA nursery Jasin, Melaka. The plot is 1 hectare that consist of 5000 of palm oil. The method is using grid line scale, stickers and phone camera to collect the data in three different layer which is outer layer, middle layer and inner layer. The data was collected for 5 weeks. These analyses have been done by using Microsoft Excel and SPSS software. The results shows that the p-value 0.000 there was a significant difference in mean assess rate of feeding damage between three factor which is outer layer, middle layer and inner layer. The result also shows that the p-value 0.000 there was a significant difference in mean damage categories between three factor which is outer layer, middle layer and inner layer. In conclusion, the purpose of controlling Apogonia sp. is to prevent crops from being destroyed and to avoid loss especially for the main nursery. Plant pests need to be prevented from main nursery before serious attacks occur. The delay in controlling causing major damage will cause the planters to suffer losses and most likely to eliminate the entire crop and replant.